THE ROLE OF LITERARY TEXT IN TEACHING THE RUSSIAN LANGUAGE (Conferencea, 2023)
A literary text is designed for emotional and sensory perception, as a result of which a person creates images using his imagination. Moreover, the text depicted by the author is refracted in the reader’s mind, and thus the reader becomes involved in the process of co-creation. This feature of an artistic text as a text of a work of art, unlike other types of text, is the presence of an aesthetic interpretation expressed in artistic images. The purpose of our research is to consider ways to develop grammatical skills at an advanced stage of teaching Russian as a foreign language using materials from literary texts and to compile a set of exercises for the development of these skills.